Penciptaan Humor pada Penampilan Stand up Comedy Indonesia (SUCI) Season 6 - Fitriyanti Bunga; Dawud Dawud (JoLLA: Journal of Language, Literature, and Arts, 2021)
Abstract: This study focuses on a form of humor creation in the form of language, logic, action, and identity utilization with social distance parameters by a comic Indra Jegel in Stand-up Comedy Indonesia (SUCI) Season 6 that is aired on Kompas TV. His skill in presenting jokes into comedy is very interesting. Many language and logic aspects that are played by Indra Jegel that make him able to produce a comedy that is not only entertaining, but also filled with moral messages to the audience. This study used a qualitative approach. The data collection technique that was used was documentation participation by collecting the data sources, observing, and transcribing into written form to ease the data observation. The results of this study showed that the process of creating humor by Indra Jegel for his stand-up comedy performance used four kinds of humor anatomy utilization which were the utilization of language, logic, action, and identity with three parameters of social distance communication. They were parameters of age, gender, and familiarity level. It was found that there were 179 data of language utilization spread into three social distance parameters, whereas there were 115 data of logic utilization. Moreover, there were 43 data of action utilization and 145 data of identity utilization spread into three social distance parameters. Keywords: humor creation; stand-up comedy; Indra Jegel Abstrak: Penelitian ini berfokus pada bentuk penciptaan humor berupa pendayagunaan bahasa, logika, aksi, dan identitas dengan parameter jarak sosial komika Indra Jegel dalam Stand up Comedy Indonesia (SUCI) Season 6 yang ditayangkan di Kompas TV. Kepiawaiannya dalam menyajikan lawakan menjadi sajian komedi sangat menarik. Banyak aspek kebahasaan dan logika yang dimainkan oleh Indra Jegel sehingga mampu melahirkan komedi yang tidak hanya menghibur, tetapi juga sarat dengan pesan-pesan moral kepada penonton. Penelitian ini menggunakan pendekatan kualitatif. Teknik pengumpulan data yang digunakan adalah dokumentasi dengan cara mengumpulkan sumber data, menyimak, dan melakukan transkrip ke dalam bentuk tulisan untuk mempermudah pengamatan data. Hasil penelitian menunjukkan bahwa proses penciptaan humor komika Indra Jegel dalam penampilan stand up comedy didapatkan empat macam pendayagunaan anatomi humor berupa pendayagunaan bahasa, logika, aksi, dan identitas dengan tiga parameter jarak sosial komunikasi, yaitu parameter usia, gender, dan tingkat keakraban. Pendayagunaan bahasa ditemukan sebanyak 179 data yang tersebar ke dalam tiga parameter jarak sosial, sedangkan pendayagunaan logika ditemukan sebanyak 115 data. Adapun pendayagunaan aksi ditemukan sebanyak 43 data yang tersebar ke dalam tiga parameter jarak sosial dan pendayagunaan identitas ditemukan sebanyak 145 data.   Kata kunci: penciptaan humor, stand up comedy, Indra Jegel